Natural plant flavonoid apigenin directly disrupts Hsp90/Cdc37 complex and inhibits pancreatic cancer cell growth and migration. (October 2015) - He, Jing; Ning, Changwen; Wang, Yu; Ma, Tianfang; Huang, He; Ge, Yubin; Liu, Jingbo; Jiang, Yiqun
Highlights: Apigenin can be digested, released and absorbed into blood circulation to accumulate. Apigenin directly inhibited Hsp90/Cdc37 interaction with structural specificity. The effect of apigenin on Hsp90/Cdc37 did not rely on CK2 activity. Apigenin induced downstream kinase client protein degradation. Apigenin induced ROS accumulation, inhibited cell proliferation and migration. Abstract: Apigenin is a common dietary plant flavonoid widely distributed in vegetables and fruits. It exhibits chemopreventive activity against various cancer cells. In this study, we demonstrated that apigenin directly blocked heat shock protein 90 (Hsp90) and cell division cycle protein 37 (Cdc37) interaction using split Renilla luciferase protein fragment-assisted complementation (SRL-PFAC) assay. Apigenin inhibited complemented Renilla luciferase (RL) activity of NRL-Hsp90/Cdc37-CRL, while its analogues did not. Apigenin also inhibited NRL-Hsp90 and Cdc37(Ser13Ala)-CRL complementation. In addition, casein kinase II (CK2) specific inhibitor 4, 5, 6, 7-tetrabromobenzotriazole (TBB) did not affect NRL-Hsp90/Cdc37-CRL complementation, indicating that the inhibitory effect of apigenin on Hsp90/Cdc37 did not rely on CK2 activity. Moreover, apigenin blocked Hsp90/Cdc37 complex and induced kinase clients protein kinase B (Akt), cyclin-dependent-kinase 4 (CDK4) and matrix metalloproteinase-9 (MMP-9) degradation and, as a consequence, induced intracellular reactive oxygen species (ROS) accumulation and inhibited cell proliferation and migration in pancreatic cancer cells.